2015
DOI: 10.1080/01459740.2015.1116528
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and the Lie in a HIV Prevention Clinical Trial

Abstract: The lie has been presented as a performance that protects identities against moral judgment in the context of power imbalances. We explore this assertion from the perspective of a pre-exposure prophylaxis trial to prevent HIV for African women in South Africa, in which context biological evidence of widespread lying about product adherence was produced, resulting in a moral discourse that opposed altruistic and selfish motivations. In this article, we seek to understand the meaning of the lie from the perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…The fears participants described in VOICE-D, and reasons for dishonesty, reflected both internalized fears of maintaining a morally sound and virtuous image to oneself, and also expressions of fear of one’s external image to staff in the clinic and members of the community. These findings resonate with those of Stadler et al, who, using a critical anthropological approach, examined qualitative data from another sub study to VOICE [19] and argued that participants engaged with the trial in a way that maintained their sense of moral wellbeing and virtuousness [15, 19]. Indeed, many of the interpretations put forward in that analysis, which were based on data collected during VOICE from 1 site [19], are directly corroborated through the quotations obtained in this post-trial study conducted at four different sites.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The fears participants described in VOICE-D, and reasons for dishonesty, reflected both internalized fears of maintaining a morally sound and virtuous image to oneself, and also expressions of fear of one’s external image to staff in the clinic and members of the community. These findings resonate with those of Stadler et al, who, using a critical anthropological approach, examined qualitative data from another sub study to VOICE [19] and argued that participants engaged with the trial in a way that maintained their sense of moral wellbeing and virtuousness [15, 19]. Indeed, many of the interpretations put forward in that analysis, which were based on data collected during VOICE from 1 site [19], are directly corroborated through the quotations obtained in this post-trial study conducted at four different sites.…”
Section: Discussionsupporting
confidence: 77%
“…Individuals’ reasons for lying are most commonly described to: avoid punishment, protect someone else or oneself from harm, win admiration, avoid embarrassment, maintain privacy, be polite or merely for the thrill of “getting away with it” [14]. Lying within the medical context has a particularly notorious reputation as an arena for deception, as our colleagues recently discussed in their anthropological analysis of participants’ behavior in the Microbicide Trials Network’s “VOICE” (MTN-003) trial [15]. The tradition of the so-called “medical lie”, in which a clinician might distort prognoses or patients may distort health-related behaviors such as medication adherence, can be further exacerbated in HIV prevention trial settings, that are characterized by complex constructs of power imbalance and moral order [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review revealed the key finding that treatment literacy, as well as calls for developing prevention literacy, has sprouted from the global South as critical to realizing the promise of biomedical innovation in resource-poor settings [41]. In sub-Saharan Africa, the controversies regarding medication misuse and concealment by participants in Project VOICE (standing for Vaginal and Oral Interventions to Control the Epidemic) offered important global lessons to biomedical researchers regarding assumptions made about significant differences in subjectivity and agency due to nationality and gender [64]. To dispel medical mistrust, a prevention literacy approach promises to generate community ownership of these prevention methods and to create the awareness of historical tensions and experiences of discrimination necessary to mitigate these social and cultural barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Around the same time, two other HIV prevention biomedical trials in women in Sub‐Saharan Africa, one of them which was stopped early, demonstrated lack of efficacy 18, 19. In some cases, blame for these outcomes was placed on the women study participants–accused of not adhering to the study products and then lying about this to trial staff 20, 21. Subsequent inquiry into these indications of sub‐optimal adherence seemed to confirm that indeed, there had been major discrepancies between self‐reported product use and pharmacokinetic measures of adherence 22.…”
Section: Putting the Gpp Guidelines To Work In Sub‐saharan African CLmentioning
confidence: 99%